Deploying and Migrating to Azure Web Apps : Optimizing Web Server Workloads - De Tender, Peter (Apress, 2019)
Learn everything you need to know to get started with Azure web apps, including deployment, key features, and benefits, to monitoring. This video introduces you to Azure App Service, and more specifically, Azure web apps. Starting from a base deployment of an Azure-running web site, you will learn about several cloud-native features of the service. These are key in allowing you to run highly available and production-ready web applications on Azure, without the underlying web server virtual machines. You will also learn about integration with Visual Studio and Visual Studio Code, to ease the overall deployment and management of such web apps from a development and sysadmin perspective. What You Will Learn Understand Azure web app core features and functionalities Deploy scalable and high-available web apps across regions Leverage Azure web app scaling features Publish web applications from Visual Studio and Visual Studio Code Run highly available web apps across multiple Azure regions Use Azure Monitor for monitoring and troubleshooting Azure web apps Who This Video Is For Developers who want a brief introduction to the value and uses of Azure web apps.